Física moderna: divulgação e acessibilidade no ensino médio através das histórias em quadrinhos - Ferreira, Rodrigo Medeiros (2013)
This work aims to show how the comics (DC comic books), when used as teaching resources, may be effective tools in the disclosure and keep students together with physics, so that we will present results of survey where the physics classes with comic were available. And while physics is directly connected with the whole technological development as we know, we also emphasize teaching Modern and Contemporary Physics (MCF) as fundamental and important role in formation of citizens.